2019
DOI: 10.12957/demetra.2019.43824
|View full text |Cite
|
Sign up to set email alerts
|

Apoio Social E Intercorrências Mamárias Em Nutrizes Que Amamentam Exclusivamente

Abstract: Objetivo: Avaliar a associação entre o apoio do cônjuge e de familiares a nutrizes assistidas em um Programa de Puericultura de um Banco de Leite Humano e as intercorrências mamárias durante o período de aleitamento materno exclusivo (AME). Métodos: Estudo transversal com 169 nutrizes assistidas pelo Programa de Puericultura de um Banco de Leite Humano em São Luís-MA. Aplicou-se um questionário semiestruturado para a coleta de dados socioeconômicos e demográficos, condições do pré-natal, apoio social e interco… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2021
2021
2021
2021

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 19 publications
0
1
0
Order By: Relevance
“…Similarly, a study reveals that the fact that women are accompanied by their husband or partner seems to have a positive influence on the duration of breastfeeding. 16 On the other hand, although the spouse is pointed out as the greatest source of support in our study, authors identified that, when breast intercurrences occur, they do not offer this support, 17 because they did not receive orientation during prenatal care on this topic, which would help them understand the situation and the difficulties of this process. 15 Thus, it is essential that prenatal care be centered on the family, that the person considered most important to the woman be identified and participate in all events held in this scenario.…”
Section: Discussionmentioning
confidence: 70%
“…Similarly, a study reveals that the fact that women are accompanied by their husband or partner seems to have a positive influence on the duration of breastfeeding. 16 On the other hand, although the spouse is pointed out as the greatest source of support in our study, authors identified that, when breast intercurrences occur, they do not offer this support, 17 because they did not receive orientation during prenatal care on this topic, which would help them understand the situation and the difficulties of this process. 15 Thus, it is essential that prenatal care be centered on the family, that the person considered most important to the woman be identified and participate in all events held in this scenario.…”
Section: Discussionmentioning
confidence: 70%